Preliminary assessment of space safety for Einstein Probe satellite - Liu, Huaqiu; Li, Fei; Hu, Jiang; Qin, Genjian; Cai, Zhiming (Journal of physics. Conference series, 2025)
The Einstein Probe (EP) satellite was deployed in a near-Earth orbit in January 2024 by Chinese scientists from the Chinese Academy of Sciences. The satellite, equipped with two payloads, aims primarily to disclose the mysteries of the early universe. In order to ensure the smooth operation of EP in space, it is essential to pay attention to the space safety of EP. Authors have carried out simulations relevant to the space safety of EP. Orbit evolution for EP has been presented; the space conjunctions between EP and other neighboring space objects are also presented. The conjunctions simulation directly supports the scientists to grasp the situation of EP in space; it also supports routine regulation staffs for EP mission to activate countermeasures to prevent EP from being in danger.